The Role Of Village Owned Enterprise (VOE) To The Rural Community Empowerment: Preliminary Review - Tri Wahyono; Arianis Chan; Ida Widianingsih; Nina Karlina (Universitas Padjadjaran, 2022)
The major problems of Indonesian rural development are unemployment, poverty, and inequality. To solve these problems, instead of giving direct financial assistance, the government prefers to facilitate the rural community on generating their own income by involving them in the economic activities through the establishment of Village Owned Enterprise (VOE). However, the establishment of VOE does not automatically empower the rural community. In many cases, VOEs compete with the existing Small and Medium Enterprises (SMEs) then fail to empower rural community. Therefore, the effectivity of VOE’s role to empower rural community is still questionable. This paper will answer above question using systematic literature review and mapping the pathways of VOE on empowering the rural community, then finds the significant variables influence the effectivity of VOE to empower the rural community. Those variables are local economic potential, community participation, and business scaling up. Since the number of VOE in Indonesia is continuously increasing but only 20 percent of them has active transactions, this study contends that scaling up the VOE business is the key issue to empower the rural community and recommends further strategy to scale up the VOE business.